Layanan Informasi Karir dalam Pengambilan Keputusan Karir Siswa Di SMA Katolik Giovanni Kupang - Liwun, Anjela Burak; Sembiring, Kristinus (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This study analyzes the role of career information services in helping students make career decisions at SMA Katolik Giovanni Kupang. Using a qualitative narrative approach, the research involved guidance and counseling (BK) teachers and 34 students from class XII-H. Data were collected through interviews and observations, then analyzed using data reduction, display, and conclusion techniques. The results showed that many students were still uncertain about choosing study majors and professions that match their interests and abilities. Factors influencing their decisions included parental influence, limited self-understanding, and lack of access to career and higher education information. Findings revealed that 79.4% of students began to understand their interests and talents, 85.3% gained knowledge about job opportunities, and 67.6% were able to make independent career decisions. BK teachers acted as facilitators and motivators, guiding students to identify their potential and connect personal values with societal needs. Despite its effectiveness, the program faced challenges such as limited technological facilities. Overall, the study concludes that career information services play a crucial role in developing students’ independence, confidence, and readiness to enter the professional world.